2021
DOI: 10.1177/11769343211016887
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Bacterial Community Involved in Bioremediation of Aged Oil-Contaminated Soil in Arid Environment

Abstract: Soil contamination by hydrocarbons due to oil spills has become a global concern and it has more implications in oil producing regions. Biostimulation is considered as one of the promising remediation techniques that can be adopted to enhance the rate of degradation of crude oil. The soil microbial consortia play a critical role in governing the biodegradation of total petroleum hydrocarbons (TPHs), in particular polycyclic aromatic hydrocarbons (PAHs). In this study, the degradation pattern of TPHs and PAHs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 87 publications
(144 reference statements)
0
2
0
Order By: Relevance
“…Microorganisms that have recently been isolated from polluted soils may have unique catabolic capabilities and the resilience of thriving in harsh environments with a dearth of nutrients (Oves et al, 2012;Rahmeh et al, 2021). These organisms, which can also fail PAHs, can provide a costeffective and viable solution for remediation (Kuppusamy et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms that have recently been isolated from polluted soils may have unique catabolic capabilities and the resilience of thriving in harsh environments with a dearth of nutrients (Oves et al, 2012;Rahmeh et al, 2021). These organisms, which can also fail PAHs, can provide a costeffective and viable solution for remediation (Kuppusamy et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, biostimulation was used for the remediation of a crude oil contaminated site via biodegradation of total petroleum hydrocarbons (TPHs) and PAHs by a consortium of bacteria observed using metagenomic analysis (Rahmeh et al, 2021). The diversity investigation revealed a group of microbes belonging to a diverse genus could be employed for remediation/restoration purposes especially in temperate regions.…”
Section: Bioremediation Of Organic Compoundsmentioning
confidence: 99%
“…The organism in this taxon was first isolated from marine sediment and mangrove soil (Liu et al, 2006;Hong et al, 2023) and was among the tropical mangrove sediment communities demonstrated to readily degrade Enteromorpha prolifera (Zhao and Ruan, 2011). Similarly, with regard to the sharp increase in population of the genus observed in treated petroleum hydrocarboncontaminated soil, Rahmeh et al (2021) attributed this surge to the less complex ring structure derivatives resulting from the degradation of aromatic compounds with complex structures. A Frontiers in Environmental Science frontiersin.org 13 critical evaluation of the metagenome data clearly showed that among the population of bacterial phyla reported across the sites, none came close to the Bacteroidetes.…”
Section: Frontiers In Environmental Sciencementioning
confidence: 99%